2019
DOI: 10.1007/s00125-019-4926-x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes as a risk factor for heart failure in women and men: a systematic review and meta-analysis of 47 cohorts including 12 million individuals

Abstract: Aims/hypothesis The prevalence of diabetes and heart failure is increasing, and diabetes has been associated with an increased risk of heart failure. However, whether diabetes confers the same excess risk of heart failure in women and men is unknown. The aim of this study was to conduct a comprehensive systematic review with meta-analysis of possible sex differences in the excess risk of heart failure consequent to diabetes. Our null hypothesis was that there is no such sex difference. Methods A systematic sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
111
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(130 citation statements)
references
References 47 publications
3
111
1
7
Order By: Relevance
“…We found a slight male disadvantage in the association between diabetes and PAD in the results Fig. 4 Multiple-adjusted ratio of women: men relative risks (RRRs) for incident coronary heart disease [8], stroke [9], vascular dementia [10], heart failure [11], and PAD, comparing individuals with diabetes to those without diabetes aggregated across cross-sectional studies, though this finding was not consistent across all included studies. The disadvantage in men may be a spurious finding resulting from the "chicken and egg" problem inherent to cross-sectional design; in addition to diabetes increasing risk for PAD, PAD is known to be a modest but independent risk factor for diabetes [42].…”
Section: Strengths and Limitationsmentioning
confidence: 85%
See 1 more Smart Citation
“…We found a slight male disadvantage in the association between diabetes and PAD in the results Fig. 4 Multiple-adjusted ratio of women: men relative risks (RRRs) for incident coronary heart disease [8], stroke [9], vascular dementia [10], heart failure [11], and PAD, comparing individuals with diabetes to those without diabetes aggregated across cross-sectional studies, though this finding was not consistent across all included studies. The disadvantage in men may be a spurious finding resulting from the "chicken and egg" problem inherent to cross-sectional design; in addition to diabetes increasing risk for PAD, PAD is known to be a modest but independent risk factor for diabetes [42].…”
Section: Strengths and Limitationsmentioning
confidence: 85%
“…Research by this team and others has provided strong evidence that, while women have lower risk for CVD overall, diabetes confers an excess relative risk in women for the onset of CVDs, including coronary heart disease, stroke, heart failure, and vascular dementia [8][9][10][11][12][13][14][15] that partially erases this female "biological advantage [16]. " The reasons for this advantage in women without diabetes compared to men of the same age are not entirely clear, but likely the result of multifactorial contributions including the protective effect of estrogen/harmful effect of testosterone, differences in cardiovascular risk factors, and sex differences in the diagnosis and treatment of diabetes and cardiovascular disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…Differences exist in cardiovascular disease biology between women and men. For example, women experience HF with preserved ejection fraction more frequently as a result of hypertension and/or diabetes, while HF with reduced ejection fraction from prior ischemic events is more frequent in men ( 25-29 ). Thus, sex-specific consideration of cardiovascular responses to abaloparatide were not encompassed by this study.…”
Section: Discussionmentioning
confidence: 99%
“…This sex discrepancy, which remains still incompletely understood, was first observed in the Framingham Heart Study, where diabetic men presented with a 2-fold, while diabetic women presented with a 4-fold increased risk of HF after adjustment for age and other CV risk factors [23]. The same finding was further confirmed in a comprehensive systematic review and meta-analysis of 47 cohorts including more than 12 million Japanese diabetic patients, which demonstrated that both type 1 diabetes mellitus (T1DM) and T2DM are stronger risk factors for HF in women than in men [24]. Potential explanations for this gender-specific effect in the epidemiology of DM-associated HF include the higher prevalence of DCM in women, the stronger correlation of DM with CHD in women, the longer exposure of women to hyperglycemia in the prediabetic state, sex-specific differences in other CV risk factors, and finally the fact that diabetic men are more prone to premature death and thus will not survive to develop HF (survival bias) [25][26][27][28].…”
mentioning
confidence: 73%